Losartan, a selective inhibitor of subtype AT1 receptors for angiotensin II, inhibits neutrophil recruitment in the lung triggered by fMLP - Raiden, Silvina Claudia (2000)
We have shown that losartan, a selective inhibitor of AT1 receptors for angiotensin II (AII), inhibits the binding of [3H]fMLP to neutrophil receptors (FPR). Here, we analyze, in Wistar rats, the effect of losartan on neutrophil recruitment in the lung triggered by fMLP. We found that i.v. infusion of losartan (0.4-20.0 microg/kg/min) inhibits neutrophil recruitment induced by i.t. instillation of fMLP, without affecting the responses induced by other stimuli, such as aggregated human IgG (aIgG), precipitating immune complexes (IC), or zymosan. Histological evaluation of lungs as well as the analysis of lung hemorrhage indices showed that losartan prevents tissue injury partially in fMLP-challenged rats. We also analyzed the effect of losartan on lung-neutrophil recruitment triggered by i.t. instillation of Pseudomonas aeruginosa. Not only was there a marked decrease in neutrophil recruitment but also a significant increase in the survival of rats instillated with Pseudomonas aeruginosa, as a consequence of losartan treatment. Our results support the notion that losartan may be useful in the treatment of certain lung inflammatory disorders associated with bacterial infectious diseases.